2014
DOI: 10.1038/ncomms5472
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing colloidal crystals by leveraging void distributions

Abstract: Colloids often crystallize into polymorphic structures, which are only separated by marginal differences in free energy. Due to this fact, the face-centred cubic and hexagonal close-packed hard-sphere morphologies, for example, usually crystallize simultaneously from a supersaturated solution. The resulting lack of long-range order in these polymorphic structures has been a significant barrier to the widespread application of these crystals in, for instance, photonic bandgap materials. Here, we report a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(109 citation statements)
references
References 46 publications
6
102
0
Order By: Relevance
“…Although these authors examined the phase transitions in the system, these were of solid-fluid nature (rather than fluid-fluid), except when monomeric LJ particles were used as solvent in place of the polymers. Also of particular relevance to our current study is the series of papers by Panagiotopoulos and co-workers [71,[85][86][87]. Mahynski et al [85] performed continuum simulations to complement their more extensive study [71] in which the polymer chains were constrained to lie on a lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these authors examined the phase transitions in the system, these were of solid-fluid nature (rather than fluid-fluid), except when monomeric LJ particles were used as solvent in place of the polymers. Also of particular relevance to our current study is the series of papers by Panagiotopoulos and co-workers [71,[85][86][87]. Mahynski et al [85] performed continuum simulations to complement their more extensive study [71] in which the polymer chains were constrained to lie on a lattice.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in our current work, we consider a system corresponding to the colloid limit, which is characterised by a size ratio q = R g /R c < 1. Subsequently, Mahynski et al have carried out continuum simulation studies of colloid-polymer mixtures wherein both colloids and polymer-chain segments were first [86] represented using repulsive LJ potentials of Weeks, Chandler and Anderson (WCA) [88] type and, in their most recent study [87], using more-general attractive potentials. Although the size ratios considered in these latter studies correspond to the colloid limit, the authors were concerned with the role played by the polymers in the crystallisation of the colloids.…”
Section: Introductionmentioning
confidence: 99%
“…We choose these specific values of M and q, because previous studies showed that the free-energy penalty to insert such a polymer greatly favours the HCP structure at sufficiently high colloid packing fraction η c [8]. We treat the polymer chains in the grand canonical ensemble, i.e., we fix the polymer fugacity z p .…”
Section: A Polymer Adsorption As a Function Of Colloid Packing Fractionmentioning
confidence: 99%
“…For large colloids, both face centered cubic (FCC) and hexagonally closed packed (HCP) structures tend to form, since the free energy difference between these two polymorphs is very small. 14 In the nanoparticle limit, when the colloids and chains become comparable in size, we 13 recently showed that colloids preferentially crystallize into the HCP structure in the presence of a dilute concentration of long enough polymers, in preference to the FCC morphology. This preference is driven by the difference in the free energy cost of confining individual polymer chains within the voids of the two different colloidal crystal morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…Over five decades of experimental, theoretical and simulation work [1][2][3][4][5][6][7][8][9][10][11][12][13] have led to the knowledge that polymer-induced depletion attractions between colloids in solution can cause them to crystallize even at low polymer concentrations. For large colloids, both face centered cubic (FCC) and hexagonally closed packed (HCP) structures tend to form, since the free energy difference between these two polymorphs is very small.…”
Section: Introductionmentioning
confidence: 99%